Suburbs under Siege - Charles M. Haar (Princeton University Press, 2014)
THIS BOOK springs from a deeply felt desire to understand and ameliorate the racial and ethnic divisions that stubbornly continue to polarize our public life. I seek, in particular, to comprehend—and to help that mythic person, the general reader, comprehend—our legal system's response to these divisions as they affect the modern American metropolis. My focus is on the intersection of two realities of post-modern society: segregation by race in metropolitan settlements, and the role the courts play in responding to the ensuing inequalities. No domestic issue is more troubling to American society today than the economic and social division between the races. While a cleavage along class and racial lines runs through many and diverse aspects of American life, nowhere is the partition more glaring or inescapable than in the gulf between the poverty and despair of central cities and the wealth and opportunity of suburbs. The exodus of jobs and mostly white middle- and upper-income people from our urban centers to suburban enclaves has split this country into two nations: one reserved for the haves, the other entrapping the have-nots. What is to be done? As a student of urbanism at a law school, heir to the Holmesian precept that the life of the law is, fundamentally, experience, I have sought to translate general concepts into concrete actions. In public service at national and state levels, I have joined with many others in efforts to bridge the gap between rhetoric and reality so as to emerge from the shadow that falls between the democratic ideal and the sober reality.